2017
DOI: 10.3390/f8100368
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Water Relations and Leaf Temperature in a Deciduous Dipterocarp Forest in Northeastern Thailand

Abstract: Deciduous dipterocarp forests across mainland Southeast Asia are dominated by two families: the Dipterocarpaceae and Fabaceae. Monsoon conditions produce strong seasonal climates with a hot dry season of 5-7 months extending from late November or early December through April or early May. Seasonal measurements of stomatal conductance and plant water potential found important differences between members of the two families. Despite their long dry season, Shorea siamensis and S. obtusa (Dipterocarpaceae) showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…ex Miq. is considered as a deciduous species in some previous studies [22,49,50], but it never showed complete deciduousness in this study site. Different letters (a,b,c,d,e) mean significant differences by Tukey's honestly significant difference (HSD) tests at 95% confidence level.…”
Section: Wood Densitymentioning
confidence: 49%
See 2 more Smart Citations
“…ex Miq. is considered as a deciduous species in some previous studies [22,49,50], but it never showed complete deciduousness in this study site. Different letters (a,b,c,d,e) mean significant differences by Tukey's honestly significant difference (HSD) tests at 95% confidence level.…”
Section: Wood Densitymentioning
confidence: 49%
“…The carbon uptake during the photosynthetically active period can thus compensate for the absence of carbon assimilation during the leafless period [53,54]. However, the stomatal conductance sharply declines when air temperature becomes higher than 40 • C. This will promote high leaf temperatures and thus reduced photosynthetic efficiency [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recognizing the plant species and their distribution within the forest is crucial for conservation efforts. Our study found that a high number of the Fabaceae family, which is dominated in the deciduous dipterocarp forests across mainland Southeast Asia (Rundel et al, 2017). Furthermore, it is essential to highlight that a bamboo species, V. ciliata A. Camus, is among the plant species discovered in the Nong Sakae Community Forest.…”
Section: Discussionmentioning
confidence: 76%
“…This work is consistent with a large body of literature regarding the biophysical controls of leaf temperature. We recognize that many aspects of plant morphology and physiology can influence T leaf relative to T air , including leaf width, foliar clumping, canopy‐scale influences on atmospheric mixing, and latent cooling from transpiration (Jarvis & McNaughton, 1986; Hadley & Smith, 1987; Smith & Carter, 1988; Leuzinger & Körner, 2007; Leigh et al ., 2012; Rundel et al ., 2017; Wright et al ., 2017; Drake et al ., 2018). However, the evidence presented here emphasizes the strong environmental control of T air on T leaf .…”
Section: Discussionmentioning
confidence: 99%